Metallized film capacitors used for EMI filtering: A reliability review. (January 2019) - Valentine, Nathan; Azarian, Michael H.; Pecht, Michael
Abstract: Metallized film capacitors are used to reduce electromagnetic interference (EMI) in electric power mains due to their high voltage capability and their open circuit failure mode, which aids in safe operation. This paper presents a comprehensive review of metallized film capacitors used for EMI filtering and their failure modes and mechanisms. One of the major failure mechanisms discussed is the corrosion of the metallized film due to moisture ingress into the package. Safety, quality, and reliability standards for metallized film capacitors are also discussed. The paper concludes with recommendations for film capacitor selection and the proper qualification and accelerated life testing to ensure long-term reliable operation.